Fluidics Jet Vectoring for Incompressible Flow by Using Counter Flow Method for Circular Duct - AlAsadi, Ali A-M. H.; Faseeh, Ahmed Hikmat (Al-Nahrain Journal for Engineering Sciences, 2017)
Computational and experimental investigation of fluidic thrust vectoring using counter-flow method had been carried out in the present work. The experimental investigation involved the design and construction of a test rig for a circular duct to examine the effect of various geometric variables on the thrust vectoring angle. The experimental tests covered Coanda surface radius R/d = (0.58823, 1.17647, 1.75471), secondary gap height h/d = (0.02941, 0.05882), over a secondary mass flow ratio range (0 ?